Problematika Keterampilan Menyimak dalam Pembelajaran Bahasa Indonesia di Kelas V SDN Pamijahan - Astri Nur Islamy (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2023)
This study aims to describe the problems of listening skills in Indonesian lessons at SDN Pamijahan. In this study, researchers used descriptive qualitative methods, data collection was carried out by means of interviews and document studies in grade 5 SDN Pamijahan